Sistemas de información geográfica preliminar del sistema de riego Campana - Malacatos - Cobos Ramón, Santiago Daniel (2019)
The present investigation was carried out in the irrigation system "Campana-Malacatos", based on existing secondary information and through the generation and updating of information, a database was developed that results in a Geographic Information System (GIS). The first phase was the collection of information in different public entities, among which the most outstanding are the Municipality of Loja (Cadastral Department) and the MAG (Dept. of Irrigation), which provided secondary information for subsequent updating; the parameters to be updated were: infrastructure of the irrigation channel, validation of the properties and road network; In addition, the use of each property and the type of irrigation it uses were verified. In the second phase, the processing of the information was carried out, ordering the database so that it is easy to use and manage for the members of the irrigation board. The GIS contains the name of the owners of each of the properties, type of crop, type of irrigation, road network, irrigation infrastructure (photographs, dimensions, survey of the entire canal and location of the most important works). In addition, aerial photographs and field trips identified the properties for recreational purposes. The resulting GIS functions as a dictionary, which serves to consult for example: the type of irrigation of each lot, owner, lots for recreational purposes; photographs of relevant works contained in the main channel will also be displayed, among others, which serve as an informative tool for the irrigation committee. Keywords: GIS, irrigation, canal, infrastructure.